Retrospective analysis of clinical characteristics and related influencing factors of Kawasaki disease. Issue 52 (30th December 2022) - Cai, Wen-Juan; Ding, Sheng-Gang
Abstract : To compare the clinical characteristics of complete Kawasaki disease (KD) and incomplete Kawasaki disease (IKD), and analyze the possible risk factors of coronary artery lesion (CAL) in KD. The clinical data of 139 children with KD admitted to the hospital from January 2016 to June 2022 were analyzed retrospectively. The differences of clinical characteristics between children with KD and children with IKD were compared. The risk factors of CAL were analyzed using univariate and multivariate logistic regression. Comparison of clinical characteristics between KD and IKD groups, the results showed there was significant difference in terms of conjunctival congestion, rash, lymph node enlargement, hand and foot redness, intravenous immune globulin non reaction and fever time ( P  < .05). Comparison of laboratory indicators between 2 groups, the results showed that there was significantly difference in the levels of neutrophils ( P  < .05). 15 cases (15.31%) in KD group were complicated with CAL, and 17 cases (41.46%) in IKD group were complicated with CAL, and the results showed there was a significant difference between the 2 groups ( P  < .05). Univariate analysis showed that the age and Hb of children with CAL were lower than those of children with nCAL, while C-reactive protein, NT-proBNP, NEUT, and ESR were higher than those of children with nCAL ( P  < .05). Multivariate analysis showed that the increase of NT-proBNP and the decrease of Hb may be independent risk factors for the occurrence of CAL in children with KD. The clinical manifestation of children with IKD is not typical. Compared with KD children, the fever time is longer and the incidence of CAL is higher. Under-age, increased NT-proBNP and decreased Hb may be independent risk factors for CAL in KD children.